The role of pelvic organs prolapse in the etiology of urinary incontinence in women - Zargham, Mahtab (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Urinary incontinence is relatively common in women and is usually associated with pelvic organs prolapse. Our aim was to determine the relationship between type and intensity of urinary incontinence and different grades and types of pelvic organ prolapse among women. MATERIALS AND METHODS: One-hundred female patients with the chief complaint of incontinence, who were diagnosed with pelvic organ prolapse participated in this study. Intensity of prolapse, stress and urge incontinence were evaluated using POP-Q (Pelvic Organ Prolapse Questionnaire), SEAPI (Stress related, Emptying ability, Anatomy, Protection, Inhibition) and Freeman criteria, respectively. RESULTS: Patients’ mean age was 51.95 ± 12.82 years. The most common type of incontinence was stress incontinence (53%) and the most common prolapse type was cystocele (76%). Cystocele and rectocele had a significant relationship with stress (P value = 0.012) and urge incontinence (P value = 0.035), respectively; however, no relationship was observed between different grades of cystocele, rectocele and enterocele with different types of urinary incontinence (P value > 0.05). In patients with urge and mixed incontinence, prolapse grade significantly increased with age, but no such relationship was found in patients with stress incontinence. The number of vaginal deliveries had a significant relationship only with cystocele and rectocele grade; however, the relationship between other variables such as intensity of different types of urinary incontinence and enterocele grade with the number of deliveries was not significant. CONCLUSION: Pelvic organ prolapse had a significant relationship with urinary incontinence regardless of intensity and POP should be examined in all of these patients.